Tandem Repeat Deletion in the Alpha C Protein of Group B Streptococcus Is recA Independent - Puopolo, Karen M. (American Society for Microbiology, 2001)
Group B streptococci (GBS) contain a family of protective surface proteins characterized by variable numbers of repeating units within the proteins. The prototype alpha C protein of GBS from the type Ia/C strain A909 contains a series of nine identical 246-bp tandem repeat units. We have previously shown that deletions in the tandem repeat region of the alpha C protein affect both the immunogenicity and protective efficacy of the protein in animal models, and these deletions may serve as a virulence mechanism in GBS. The molecular mechanism of tandem repeat deletion is unknown. To determine whether RecA-mediated homologous recombination is involved in this process, we identified, cloned, and sequenced the recA gene homologue from GBS. A strain of GBS with recA deleted, A909ΔrecA, was constructed by insertional inactivation in the recA locus. A909ΔrecA demonstrated significant sensitivity to UV light, and the 50% lethal dose of the mutant strain in a mouse intraperitoneal model of sepsis was 20-fold higher than that of the parent strain. The spontaneous rate of tandem repeat deletion in the alpha C protein in vitro, as well as in our mouse model of immune infection, was studied using A909ΔrecA. We report that tandem repeat deletion in the alpha C protein does occur in the absence of a functional recA gene both in vitro and in vivo, indicating that tandem repeat deletion in GBS occurs by a recA-independent recombinatorial pathway.